2022
DOI: 10.1111/cbdd.14161
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine attenuates lipopolysaccharide‐induced inflammation and apoptosis of WI‐38 cells by reducing glutathione S‐transferase M1 expression

Abstract: Pediatric pneumonia is an infectious lung disease with high morbidity and mortality. Sinomenine, an alkaloid extracted from Caulis Sinomenii, exerts anti‐inflammatory and anti‐apoptotic activities. Lipopolysaccharide (LPS) is widely used for the establishment of an inflammatory model. This research aimed to explore the influences of sinomenine on LPS‐caused inflammatory injuries in fetal lung WI‐38 cells. WI‐38 cells were treated with LPS to establish a cellular model of pediatric pneumonia. Cell viability was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Y. Liu and team reported on the treatment of SIN in children with pneumonia. Their results showed that SIN (5–20 µM) inhibited glutathione S-transferase M1 (GSTM1), decreased TNF-α, IL-1β, and MCP-1, and increased IL-10, thereby alleviating inflammation and apoptosis in lipopolysaccharide (LPS)-stimulated WI-38 cells [ 130 ].…”
Section: Anti-inflammatory Activity and Analgesic Activitymentioning
confidence: 99%
“…Y. Liu and team reported on the treatment of SIN in children with pneumonia. Their results showed that SIN (5–20 µM) inhibited glutathione S-transferase M1 (GSTM1), decreased TNF-α, IL-1β, and MCP-1, and increased IL-10, thereby alleviating inflammation and apoptosis in lipopolysaccharide (LPS)-stimulated WI-38 cells [ 130 ].…”
Section: Anti-inflammatory Activity and Analgesic Activitymentioning
confidence: 99%
“…Activation of the caspase-3 pathway has been considered a pivotal event during cell apoptosis (Y. Liu et al, 2022;Singh et al, 2023) A permeable fluorogenic caspase substrate, Su-perView™ 488 Caspase-3 Assay Kit for Live Cells (Yeasen Biotechnology, China), can detect caspase-3 within live cells. Transfected or non-transfected SW620 or HCT 116 cells were cultured in black 96-well plates with the addition of curcumin or not for 72 h. Then, a fresh medium containing 5 μM SuperView 488 Substrate was added to replace the old medium.…”
Section: In Vitro Caspase-3 Activity Assaymentioning
confidence: 99%